The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1038/s41598-018-34016-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the distribution of load on the lower limbs and balance before and after ankle arthrodesis with the Ilizarov method

Abstract: Ankle arthrodesis with the Ilizarov method is an accepted form of treatment of advanced degenerative changes of the ankle joint. Incorrect balance and load distribution on the lower limbs may result in pain and dysfunction. The aim of the study was to assess the change of balance and load distribution in lower extremities in patients before and after ankle arthrodesis with the Ilizarov method. Between 2013 and 2016, ankle arthrodesis using the Ilizarov method was performed on 21 patients. The evaluation of bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…A pedobarographic platform from Zebris ® Medical GmbH was used to evaluate plantar load distribution of the lower limbs (Kalron, Nitzani, & Achiron, ; Morasiewicz, Konieczny, et al, ; Morasiewicz, Urbański, et al, ). The platform was equipped with 1,504 sensors and connected to a PC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pedobarographic platform from Zebris ® Medical GmbH was used to evaluate plantar load distribution of the lower limbs (Kalron, Nitzani, & Achiron, ; Morasiewicz, Konieczny, et al, ; Morasiewicz, Urbański, et al, ). The platform was equipped with 1,504 sensors and connected to a PC.…”
Section: Methodsmentioning
confidence: 99%
“…Each patient underwent the test three times and the average scores of these measurements were recorded for further analysis (Ko & Lee, ). The Zebris FDM software (https://www.zebris.de/en/) was used to process and record pressure parameters that were later subjected to statistical analysis (Kalron et al, ; Morasiewicz, Konieczny, et al, ; Morasiewicz, Urbański, et al, ). In the Zebris FDM software, the pressure map of plantar load distribution was created (Figure b; Ko & Lee, ; Morasiewicz, Konieczny, et al, ; Morasiewicz, Urbański, et al, ; Soltani et al, ) 19–22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial by Zheng et al [24] showed that 3DPMassisted surgical planning had shorter operation duration, less blood loss and X-ray exposure, as well as better anatomic reduction and clinical outcomes than conventional surgery in 100 patient with Pilon fractures. However, few studies have used 3DPM in combination with external xators for the treatment of lower extremity deformity [25,26,27]. To the best of our knowledge, no study has reported the application of 3DPM in the correction of PAC with external xators.…”
Section: D Printed Modelsmentioning
confidence: 99%
“…When assessing the outcomes from the treatment of lower limb diseases, it is important to evaluate the limb function in addition to routine clinical and radiological assessment [3], [5], [6], [23]. From the orthopaedic and patient point of view, after the treatment, an assessment should be carried out of the biomechanics of the musculoskeletal system [5], [6], [17], [23]- [25].…”
Section: Introductionmentioning
confidence: 99%